2006
DOI: 10.1093/bja/ael134
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of carbon dioxide during laparoscopy in children measured using a novel mass spectrometric technique

Abstract: After 10 min of laparoscopy 10-20% of expired CO(2) derives from the exogenous CO(2). CO(2) absorption can be measured using a simple mass spectrometric technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Specifi c complications from MIS in neonates relate to hypercarbia, desaturation, hypotension, metabolic acidosis, and hypothermia and are seen more often during thoracoscopic procedures [ 43 ]. During laparoscopic surgery, the pneumoperitoneum or pneumothorax is created and maintained by insuffl ating carbon dioxide (CO 2 ), which results in signifi cant absorption of CO 2 into the circulation.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifi c complications from MIS in neonates relate to hypercarbia, desaturation, hypotension, metabolic acidosis, and hypothermia and are seen more often during thoracoscopic procedures [ 43 ]. During laparoscopic surgery, the pneumoperitoneum or pneumothorax is created and maintained by insuffl ating carbon dioxide (CO 2 ), which results in signifi cant absorption of CO 2 into the circulation.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…During laparoscopic surgery, the pneumoperitoneum or pneumothorax is created and maintained by insuffl ating carbon dioxide (CO 2 ), which results in signifi cant absorption of CO 2 into the circulation. Insuffl ated CO 2 may contribute up to 30 % of the exhaled CO 2 during thoracoscopic procedures and up to 20 % during laparoscopic surgery [ 43 ]. As a result, high levels of arterial CO 2 may be reached [ 44 -47 ].…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…For this reason, more careful observation is recommended in smaller children during and immediately following laparoscopic procedures. Pacilli et al (2006) demonstrated that in children after 10 -12mins of laparoscopy, 10-20% of expired carbondioxide derived from absorption of exogenous carbon dioxide and continues to be eliminated for up to 30minutes after the end of insufflation. Minute ventilation needs to be www.intechopen.com adjusted in order to avoid hypercarbia.. McHoney et al (2003) observed the elimination of carbon dioxide in children to be age-dependent.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Both of which have been suggested to be exacerbated by absorption of CO 2 insufflation for MIS, especially in neonates with CDH with hypoplastic lungs [48] . In addition, CO 2 insufflation may raise intracavity pressures and limit venous return and end-organ perfusion.…”
Section: Surgical Approachmentioning
confidence: 99%